MRNA-binding proteins and cell cycle progression. Issue 8 (August 2022) - Polymenis, Michael
Abstract : Proteins that bind to each mRNA may affect the latter's abundance and location in the cell and how well ribosomes will translate that mRNA into a protein. Hence, mRNA-binding proteins (mRBPs) represent obvious control points in gene expression. Surprisingly, little is known about mRBPs and cell-cycle progression.